Promoter orientation within an AAV-CRISPR vector affects Cas9 expression and gene editing efficiency - Fry, LE; Peddle, CF; Stevanovic, M; Barnard, AR; McClements, ME; MacLaren, RE (Mary Ann Liebert Inc, 2020)
Adeno-associated virus (AAV) vectors have been widely adopted for delivery of CRISPR-Cas components, especially for therapeutic gene editing. For a single vector system, both the Cas9 and guide RNA (gRNA) are encoded within a single transgene, usually from separate promoters. Careful design of this bi-cistronic construct is required due to the minimal packaging capacity of AAV. We investigated how placement of the U6 promoter expressing the gRNA on the reverse strand to SaCas9 driven by a cytomegalovirus promoter affected gene editing rates compared to placement on the forward strand. We show that orientation in the reverse direction reduces editing rates from an AAV vector due to reduced transcription of both SaCas9 and guide RNA. This effect was observed only following AAV transduction; it was not seen following plasmid transfection. These results have implications for the design of AAV-CRISPR vectors, and suggest that results from optimizing plasmid transgenes may not translate when delivered via AAV.